Political representation in Southern Europe and Latin America: Crisis or Continuing Transformation? - Freire, A.; Mélany Barragán; Coller, X.; Coller, X.; Lisi, M.; Marco Lisi; Emmanouil Tsatsanis; Tsatsanis, E. (2020)
André Freire, Mélany Barragan, Xavier Coler, Marco Lisi & Emmanouil Tsatsanis (editors) (2020), Political representation in Southern Europe and Latin America. Before and After the Great Recession and the Commodity Crisis., Edited volume for Routledge book series “Routledge Research on Social and Political Elites”, 2020.